SENTENCE STRUCTURES OF INDONESIAN AND TETUN: A REVIEW IN THE CONTEXT OF BIPA IN TIMOR LESTE - REIS, ALEXANDRE DOS; Idris, Nuny S.; Rizkyanfi, M. W. (SYNTIFIC, 2025)
Background. Teaching Indonesian as a Foreign Language (BIPA) in Timor Leste presents certain challenges due to differences in sentence structures between Indonesian and Tetun. A thorough understanding of these similarities and differences is essential to improve the effectiveness of BIPA instruction. Research Purpose. This study aims to analyze the comparative sentence structures of Indonesian and Tetun and their implications for teaching BIPA in Timor Leste. Research Method. This qualitative study employs a contrastive analysis method, with data consisting of sentence structures from both languages examined in detail. Findings. The results reveal significant differences in the word order of possessive noun phrases and the use of grammatical particles, which can cause negative interference for BIPA learners whose native language is Tetun. However, similarities in basic sentence patterns, such as the Subject-Predicate-Object (S-P-O) structure, can facilitate the learning process. Conclusion. The study recommends that BIPA instructors develop teaching modules focusing on the sentence structure differences that pose difficulties, particularly those causing negative interference, to enhance the effectiveness of teaching Indonesian to Tetun-speaking learners. Keywords: Sentence Structure, Indonesian, Tetun, BIPA, Contrastive Analysis